A set of plasmatic microRNA related to innate immune response highly predicts the onset of immune reconstitution inflammatory syndrome in tuberculosis co-infected HIV individuals (ANRS-12358 study) - Pean, Polidy; Meng, Ratana; Benichou, Eliott; Srey, Pichsivannary; Dim, Bunnet; Borand, Laurence; Marcy, Olivier; Laureillard, Didier; Blanc, François-Xavier; Cantaert, Tineke; Madec, Yoann; Weiss, Laurence; et al. (Frontiers in Immunology, 2025)
BackgroundAfter initiation of combination antiretroviral treatment (cART), HIV-1/tuberculosis coinfected patients are at high risk of developing tuberculosis-associated immune reconstitution inflammatory syndrome (TB-IRIS). MicroRNAs, small molecules of approximately 22 nucleotides, which regulate post-transcriptional gene expression and their profile has been proposed as a biomarker for many diseases. We tested whether the microRNA profile could be a predictive biomarker for TB-IRIS.MethodsTwenty-six selected microRNAs involved in the regulation of the innate immune response were investigated. Free plasmatic and microRNA-derived exosomes were measured by flow cytometry. The plasma from 74 HIV-1+TB+ individuals (35 IRIS and 39 non-IRIS) at the time of the diagnosis and before any treatment (baseline) of CAMELIA trial (ANRS1295-CIPRA KH001-DAIDS-ES ID10425); 15 HIV+TB− and 23 HIV−TB+, both naïve of any treatment; and 20 HIV−TB− individuals as controls were analysed.ResultsAt baseline, both IRIS and non-IRIS HIV+/TB+ individuals had similar demographic and clinical characteristics, including sex, age, body mass index, very low CD4+ cell counts (27 cells/mm3), and plasma HIV RNA load levels (5.76 log copies/ml). Twenty out of 26 plasmatic-microRNAs tested were no different between IRIS and controls. Twelve of the 26 tested microRNAs showed statistically significant differences between IRIS and non-IRIS patients (p-values ranging from p <0.05 to p <0.0001). Among these, five could discriminate between IRIS and non-IRIS individuals using ROC curve analysis (AUC scores ranging from 0.74 to 0.92). The combination of two (hsa-mir-29c-3p and hsa-mir-146a-5p) or three microRNAs (hsa-mir-29c-3p, hsa-mir-29a-3p, and hsa-mir-146a-5p) identified IRIS with 100% sensitivity and high specificity (95% and 97%, respectively).ConclusionThe combination of at least two or three plasmatic microRNAs known to regulate inflammation and/or cytokine responses could be used as biomarkers to discriminate IRIS from non-IRIS in HIV-TB co-infected individuals at the time of diagnosis and prior to any treatment.